Progress in studying the impact of hyperlipidemia and statins on rotator cuff injury and repair - Qian, Yinhua; Huang, Haoqiang; Wan, Renwen; Zhou, Yu; Feng, Xinting; Xu, Feng; Luo, Zhiwen; Wang, Qing (Frontiers in Public Health, 2023)
This review delves into the intersection of two prevalent conditions, hyperlipidemia and rotator cuff injuries, both of which bear substantial healthcare burdens. Our investigation begins with an exploration of rotator cuff injuries, common musculoskeletal disorders that severely impair shoulder functionality and quality of life. These injuries are notably pervasive among sports enthusiasts and the older adult, with an incidence rate estimated at 5–10% in the general population. Despite their widespread occurrence and the diverse, multifactorial etiological factors, effective treatment strategies remain elusive. We then examine hyperlipidemia, a metabolic disorder affecting approximately 40% of the global adult population. Characterized by elevated levels of cholesterol and triglycerides, hyperlipidemia can precipitate severe cardiovascular complications and presents a significant socioeconomic burden. Although current management strategies encompass lifestyle modifications and pharmacological interventions, the condition remains a formidable health challenge. Central to this review is the exploration of a potential association between hyperlipidemia and rotator cuff injuries. We aim to synthesize the current understanding of hyperlipidemia’s role in the pathophysiology of rotator cuff injuries, thereby offering fresh insights into their common etiological underpinnings, potential therapeutic targets, and drugs, such as Statins. The influence of other lipid-lowering therapeutics on tendon health is also considered, and further research into the molecular pathways and potential therapeutic benefits of these drugs is required. This pursuit aligns with broader efforts to enhance patient outcomes, minimize healthcare burdens, and contribute to the global understanding of these prevalent conditions.